Feminist Counterwritings: Education of Stone Girls - de Oliveira, Rosemary Rodrigues [UNESP]; dos Anjos Rocha, Késia; Oliveira, Érika Cecília Soares (FapUNIFESP (SciELO), 2022)
In this article, we invite you to think outside the colonial boxes of academic writing from the experience of a train trip. In its wagons we are, authors of this narrative: two black women and a white one. Our purpose is to produce a policy of alliance between women in combating racism. Though it is about polyphonic talk, the protagonist of this story is the first author and it is in her cabin that this counterwriting gestated in the heart of the global south takes place. It is by means of her memory work that we talk about the exclusions that cross the black girls’ bodies during their schooling processes. It results from this lesson the observation of the production of stone girls’ ranks, apart from formal education. Here, our thought is anchored in feminist theorizations and, at every station, we rewrite the official history, register the fights and build a common future
Contraescrituras feministas: la educación de las niñas de piedra
Contraescritas feministas: educação das meninas de pedra
Keywords: Black women; Counterwriting; Education; Memory; Subaltern feminisms